Manajemen Kepala Sekolah dan Guru dalam Meningkatkan Kualitas Pembelajaran dengan Mengimplementasikan Nilai-Nilai Moderasi Beragama di UPT Satuan Pendidikan SDN Ngadirejo 1 Kecamatan Tutur Kabupaten Pasuruan - Fitriya, Evi; Tharaba, M. Fahim; Muniry, Samsul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
"Indonesia is a country rich in diversity, such as ethnicity, religion, culture, and language. This diversity can be both a potential and a challenge in maintaining social harmony. In this context, Islam offers four main principles that are key to maintaining peaceful coexistence amidst diversity: Tasamuh (tolerance), Musawah (equality), Tawasuth (moderation),and Ukhuwah (fraternity/brotherhood). This article discusses the management of school principals and teachers in improving the quality of learning by implementing the values of religious moderation in schools with students of different religions."